Heterotopic Neurogenesis in a Rat with Cortical Heterotopia - Lee, Kevin S. (J Neurosci, 1998)
Early cellular development was studied in the neocortex of the tish rat. This neurological mutant is seizure-prone and displays cortical heterotopia similar to those observed in certain epileptic patients. The present study demonstrates that a single cortical preplate is formed in a typical superficial position of the developing tish neocortex. In contrast, two cortical plates are formed: one in a normotopic position and a second in a heterotopic position in the intermediate zone. As the normotopic cortical plate is formed, it characteristically separates the subplate cells from the superficial Cajal-Retzius cells. In contrast, the heterotopic cortical plate is not intercalated between the preplate cells because of its deeper position in the developing cortex. Cellular proliferation occurs in two zones of the developing tish cortex. One proliferative zone is located in a typical position in the ventricular/subventricular zone. A second proliferative zone is located in a heterotopic position in the superficial intermediate zone, i.e., between the two cortical plates. This misplaced proliferative zone may contribute cells to both the normotopic and heterotopic cortical plates. Taken together, these findings indicate that misplaced cortical plate cells, but not preplate cells, comprise the heterotopia of the tish cortex. Heterotopic neurogenesis is an early developmental event that is initiated before the migration of most cortical plate cells. It is concluded that misplaced cellular proliferation, in addition to disturbed neuronal migration, can play a key role in the formation of large cortical heterotopia.